L-Arginine effectively alleviates doxorubicin-induced cardiac dysfunction by inhibiting myocardial fibrosis - Mo-li Zhu; Rui Hao; Meng-yao Zhao; Pei-yao Liu; Hong-dou Zhang; Peng Li; Ya-ling Yin; Hui-jun Liu; Guang-qiu Ren; Jie Zhang; Jing Yang (Molecular Biology Reports, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Preparation of P507-containing monodisperse magneto-permeable polystyrene swelling microspheres for extraction of low-concentration scandium from simulated red mud liquor - Jie Wang; Jinghan Ren; Rui Feng; Chenxi Li; Chenxin Shi; Mingqi Guo; Tianlei Yang; Yueping Guan (Journal of Water Process Engineering, 2026)

Structure, assembly, and biological assessment of microbial communities based on eDNA metabarcoding in the continuous river-estuary-sea system of the Yellow River Estuary, China - Gang Xie; Xiaoxia Yu; Ning Zhang; Jie Li; Rui Wang; Yu Wang; Xinlei Li; Dan Li; Wanting Wang; Shilong Ren; Yi Zhu; Guoqiang Wang (Marine Pollution Bulletin, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Three-Dimensional Fast Marching Seismic Traveltime Computation Based on Coarse-Grid Interpolation - Yan-song Li; Jun-jie Yang; Xue-feng Gao; Hui Sun; Yun Long; Peng Lin; Song-da Ji; Hong-yong Ren; Rui Chen (Applied Geophysics, 2026)

Inhibiting NAT10 suppresses hepatocellular carcinoma progression by reducing Nrf2 mRNA stability and increasing oxidative stress - Wei Gu; Ziyi Ren; Jie Gao; Ziyi Shen; Yuanhui Wang; Luanqi Xu; Rui Qian; Qinyi Miao; Yifan Wu; Xiaomeng Hu; Yan Wu; Wei Liu; et al. (Chemico-Biological Interactions, 2026)

Editor's note to “Variation and driving mechanism analysis of water footprint efficiency in crop cultivation in China” [Sci. Total Environ., Volume 725 (2020) 138537] - Xinchun Cao; Rui Shu; Jie Ren; Mengyang Wu; Xuan Huang; Xiangping Guo (Science of The Total Environment, 2025)

Influence and mechanism of polyethylene microplastics on antibiotic resistance genes and microbial community in sludge composting process - Jie Yang; Rui Jiang; Yingchun Li; Weijian Liu; Mengmeng Wang; Peng Ren (Journal of Environmental Chemical Engineering, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Research and analysis on safety design of AI technology applied to space system - Shengxin Jiang; Jie Gao; Rui Zhang; Xinhua Zhang; Wei Zhu; Liming Ren (Journal of Space Safety Engineering, 2025)

Gradient distribution of trap states in polymer dielectrics induced by electric field for enhanced insulation properties - Bing Xia; Ming-Xiao Zhu; Zhi-Hao Xing; Rui Liu; Jie-Rui Ren; Xue-Kai Xu (Chemical Engineering Journal, 2025)

Unravelling spatiotemporal heterogeneity of wildfire carbon dioxide emissions in Southeast Asia: based on a high-resolution inventory - Lei Xia; Changxu Ren; Yongling Yang; Jie Li; Wenxuan Fan; Rui Liu (Journal of Environmental Management, 2025)

Different effects of bio/non-degradable microplastics on sewage sludge compost performance: Focusing on antibiotic resistance genes, virulence factors and key metabolic functions - Xiangyu Liu; Huiyue Li; Jie Yang; Shen Yan; Yufei Zhou; Rui Jiang; Renhe Li; Mengmeng Wang; Peng Ren (Journal of Hazardous Materials, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

The integrating optional energy band alignment and oxygen vacancies over α/β-Fe2O3-3R homogenic boundary boosted self-fenton degradation of antibiotics - Jing Yan; Shi-Xian Guan; Ying Li; Jing Guo; Na Zhang; Jian-Yong Zhang; Chun-Wei Guo; Jie Ren; Qin-Fei Ke; Yong-Zheng Fang; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Recent progress in Cu-based electrocatalysts for CO2 reduction - Ruo-Zheng Xiong; Hui-Min Xu; Hong-Rui Zhu; Zhi-Jie Zhang; Gao-Ren Li (Chemical Engineering Journal, 2025)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Myo-inositol: A potential game-changer in preventing gill cell death and alleviating “gill rot” in grass carp (Ctenopharyngodon idellus) - Jie Chen; Wei-Dan Jiang; Lin Feng; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Rui-Nan Zhang; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

Corrigendum to “Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa)” J Hazard Mater 469(2024) 133862 - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Brassinosteroid decreases cadmium accumulation via regulating gibberellic acid accumulation and Cd fixation capacity of root cell wall in rice (Oryza sativa) - Jie Ya Sun; Rui Guo; Qi Jiang; Chang Zhao Chen; Yong Qiang Gao; Meng Meng Jiang; Ren Fang Shen; Xiao Fang Zhu; Jiu Huang (Journal of Hazardous Materials, 2024)

Key factors controlling nitrogen transformation and efflux at the sediment–water interface: a comparative study from different trophic reservoirs - Jie Ren; Guilin Han; Xiaolong Liu; Rui Qu; Ziyang Ding (Journal of Soils and Sediments, 2024)

Promotion of anaerobic biodegradation of azo dye RR2 by different biowaste-derived biochars: Characteristics and mechanism study by machine learning - Yu-Qian Wang; Jie Ding; Ji-Wei Pang; Chuan-Dong Wu; Han-Jun Sun; Rui Fang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2024)

Photocatalytic degradation of benzotriazole through synergy of electron donor–acceptor units and Au clusters in covalent organic frameworks - Hui Wang; Yuhan Xiong; Yi He; Lingru Kong; Lan Ding; Rui Wu; Xin-Lei Gao; Jie Ding; Nanqi Ren (Chemical Engineering Journal, 2024)

Roxarsone biotransformation by a nitroreductase and an acetyltransferase in Pseudomonas chlororaphis, a bacterium isolated from soil - Jie-wen Ma; Gui-wen Liu; Jia-Yu Zhai; Ke-qian Zhao; Ya-qing Wu; Rui-lian Yu; Gong-ren Hu; Yu Yan (Chemosphere, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

pCtFSG2, a flower-specific promoter with suitable promoter activity in safflower - Jiang Chen; Chaoxiang Ren; Jie Wang; Bin Xian; Rui Wang; Qinghua Wu; Jin Pei (Journal of Plant Biochemistry and Biotechnology, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Inhibitory effect of polyethylene microplastics on roxarsone degradation in soils - Jie-wen Ma; Ya-qing Wu; Chen-Lu Xu; Zhuan-xi Luo; Rui-lian Yu; Gong-ren Hu; Yu Yan (Journal of Hazardous Materials, 2023)

Insight into the roles of microalgae on simultaneous nitrification and denitrification in microalgal-bacterial sequencing batch reactors: Nitrogen removal, extracellular polymeric substances, and microbial communities - Yaruo Jin; Wei Zhan; Rui Wu; Yahong Han; Shanshan Yang; Jie Ding; Nanqi Ren (Bioresource Technology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Pollution characteristics and health risk assessment of polycyclic aromatic hydrocarbons and nitrated polycyclic aromatic hydrocarbons during heating season in Beijing - Xurong Bai; Jie Wei; Yanqin Ren; Rui Gao; Fahe Chai; Hong Li; Fei Xu; Yuxue Kong (Journal of Environmental Sciences, 2023)

One-dimensional copper bromide based inorganic-organic hybrids as fuels for hypergolic bipropellants with hydrogen peroxide as oxidizer - Ya-Jie Wang; Xu-Yang Wang; Hong Xu; Wei-Wei Ren; Rui Pang; Li Yang; Wen-Chao Tong; Qian-You Wang; Shuang-Quan Zang (Chemical Engineering Journal, 2023)

Development of a matrix-based candidate reference material for human glycated albumin using isotope-dilution liquid chromatography/tandem mass spectrometry - Rui Zhang; Rui Zhao; Wenhua Ren; Mo Wang; Gaowei Fan; Jie Shi; Yichuan Song; Xiaojie Zhou; Qingtao Wang (Analytica Chimica Acta, 2023)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.